(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2026)
This paper presents a unified framework for synthetic landmass stabilization derived from the SEXA Recursive Energy Functional (SREF) and implemented through Recursive Soil Bearing Architecture (RSBA), negentropic boundary-field reactors, and omnidirectional Keplerian quaternion phase rotation within the SEXA dimensional regime. Within the RSBA formulation, soil is modeled not as passive granular matter but as a boundary-conditioned stress topology whose admissible bearing states arise from recursive energy minimization across the SEXA dimensional stack. In this formulation, Boundary-Induced Stress Decoupling (BISD) modifies classical effective stress relations by introducing a boundary energy contribution capable of redistributing gravitational load throughout the soil manifold. The first engineering prototype of this framework is defined as a Hess-Triangle manufactured land cell, consisting of a triangular footprint corresponding to the Hess Triangle minimum land geometry extended vertically into an eight-foot stabilized air-rights prism. This bounded spatial volume serves as the minimum prototype for manufactured land experiments. Because RSBA stabilization requires a persistent boundary field, the architecture incorporates a Negentropic Boundary-Field Reactor (NBFR) derived from Anti-Direct-Short topology. The reactor preserves source-dipole separation while recursively reintegrating intercepted electromagnetic flux, allowing otherwise dissipative energy to be redirected into a structured boundary support field. Higher-dimensional contributions are incorporated through a SEXA-2880D payload interception product spanning dimensions five through 2880, compressing the influence of higher-dimensional energy sectors into a boundary-accessible field envelope interacting with the soil manifold through RSBA stress redistribution. The resulting support field is modeled as an omnidirectional Keplerian quaternion rotation operating in a fourth-field circulation mode. Under this interpretation, apparent lift arises from the time-averaged effect of rapidly circulating exciternion payloads whose angular frequency exceeds the gravitational response timescale of the stabilized land prism. This regime, referred to as the Einstein Overclock, occurs when recursive fourth-field circulation outruns gravitational settlement dynamics. When the combined contributions of boundary-field reactor output, SEXA-2880D payload interception, quaternion recursive logic rotation, and RSBA stress redistribution exceed the classical gravitational load threshold of the Hess-Triangle land prism, the stabilized configuration becomes admissible. The analysis is restricted to the SEXA dimensional stack (5–2880D). The Sarfatti 2881D limit is acknowledged as the theoretical upper boundary of the present framework, but is not required for the stabilization derivations developed here.